Pengembangan dan Evaluasi Minuman Sereal Sarapan Kaya Zat Gizi Berbasis Kedelai, Oat, Kelor, dan Madu untuk Remaja: Development and Evaluation of a Nutrient-Rich Breakfast Cereal Beverage Based on Soybeans, Oats, Moringa, and Honey for Adolescents - Puspaningrum Dwi Hartanti; Ibnu Malkan Bakhrul Ilmi (Amerta Nutrition, 2025)
Background: Adolescence is a period of growth spurt, requiring optimal nutrient intake to support physical and cognitive development. Skipping breakfast increases the risk of growth faltering and reduced academic performance. In West Java, 6.1% of adolescents aged 13-15 years are underweight and 29.6% exhibit poor breakfast habits, which may hinder the achievement of the SDGs, particularly Zero Hunger and Good Health and Well-Being. Objectives: To analyze the organoleptic acceptability and nutritional content of cereal beverage formulated from soybeans, rolled oats, moringa leaves, and randu honey as a potential nutrient source for adolescents. Methods: A completely randomized design with three formulations was used. The ratio of soybean powder to rolled oats were F1 (20g:10g), F2 (15g:15g), and F3 (10g:20g). Each formulation was supplemented with 5 g of moringa leaf powder and 10 g honey. Organoleptic data were analyzed using Kruskal-Wallis and Mann-Whitney tests, while nutritional content from proximate and mineral analysis were evaluated using ANOVA and Duncan tests. Results: Significant differences were observed in color(p-value=0.048) and texture (p-value=0.012), while aroma and taste did not differ significantly (p-value>0.05). Nutritional analysis showed significant differences in ash (p-value=0.002), moisture (p-value=0.003), energy (p-value=0.002), protein (p-value<0.001), fat (p-value=0.001), carbohydrates (p-value<0.001), and calcium (p-value<0.001), whereas iron content showed no significant difference (p-value=0.102). Conclusions: F1 was selected as the best formulation, containing 23,79 g of protein per 100 g, making it a high-protein product. This cereal beverage shows potential as a practical and nutritious breakfast alternative for adolescents.